The Impact of European Traffic Policy and Traffic Routes on the Development of the Ports of Rijeka and Place - Ivaković, Čedomir; Kolanović, Ines; Šantić, Livia (Promet - Traffic&Transportation, 2006)
Sea ports are the key segment of the traffic and economicdevelopment of maritime countries. Pan-European transportcorridors include the most important sea pmts and sea routes.They are an extension of the existing land corridors.The most important and the most promising crossings oftraffic corridors between the Central European, Pannonianand Adriatic areas, with the naturally shortest traffic routes directedtowards the Croatian sea ports are Corridor 58 ( Rijeka-Zagreb-Budapest) and Corridor 5c (Ploce-Sarajevo-Osijek–Budapest). The primary purpose of this work is to study the importanceof the existing trading conditions and new investmentundertakings in the context of increase in competitiveness of theports of Rijeka and Place.The authors’ attention is particularly directed to the constructionof new port terminals to increase the traffic potentialsof the Croatian sea ports. The formed conception with its characteristics,the methodology applied, and research results representthe quality starting points in determining a uniform portpolicy of the Republic of Croatia within the European trafficsystem.